Analisis Metode Just-In-Time untuk Efisiensi Supply Chain Makan Bergizi Gratis - Dien Annisahul Husna; Indah Setia Utami (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
This research is motivated by the logistical challenges of a large-scale nutritious meal program that requires precise distribution and cost efficiency. This case study analyzes the application of the Just-In-Time (JIT) Hybrid method in supply chain management at the Somagede Nutrition Fulfillment Service Unit (SPPG) to optimize operations and budget accountability. The research method uses a descriptive qualitative approach through in-depth interviews and document analysis of the Dialur application on the National Nutrition Agency’s digital platform. The findings indicate that the Dialur application (Provision and Distribution) plays a central role in digital control and transparent financial realization. The results show that digital integration and the application of JIT Hybrid in the procurement of daily fresh ingredients and reserve stock management can minimize technical waste through accurate synchronization of beneficiary data, while increasing accountability in the management of public nutrition programs.